Implications of bulk water transfer on local water management institutions: A case study of the Melamchi Water Supply Project in Nepal - Pant, Dhruba; Bhattarai, Madhusudan; Basnet, Govinda (International Food Policy Research Institute, 2008)
To mitigate a drinking water crisis in Kathmandu valley, the Government of Nepal initiated the Melamchi Water Supply Project in 1997, which will divert water from the Melamchi River to Kathmandu city's water supply network. In the first phase, the Project will divert 170,000 cubic meters of water per day (at the rate of 1.97M3/sec), which will be tripled using the same infrastructure as city water demand increases in the future. The large scale transfer of water would have farreaching implications in both water supplying and receiving basins. This paper analyzes some of the major changes related to local water management and socioeconomics brought about by the Project and in particular the changes in the local water management institutions in the Melamchi basin. Our study shows that traditional informal water management institutions were effective in regulating present water use practices in the water supplying basin, but the situation will vastly change because of the scale of water transfer, and power inequity between the organized public sector on one side and dispersed and unorganized marginal water users on the other. The small scale of water usage and multiple informal arrangements at the local level have made it difficult for the local users and institutions to collectively bargain and negotiate with the central water transfer authority for a fair share of project benefits and compensation for the losses imposed on them. The process and scale of project compensation for economic losses and equity over resource use are at the heart of the concerns and debates about the Melamchi water transfer decision. The Project has planned for a one-time compensation package of about US$18 million for development infrastructure related investments and is planning to share about one percent of revenue generated from water use in the city with the supplying basin. The main issues here are what forms of water sharing governance, compensation packages, and water rights structures would emerge in relation to the project implementation and whether they are socially acceptable ensuring equitable distribution of the project benefits to all basin communities. In addition, these issues of the Melamchi project discussed in this paper are equally pertinent to other places where rural to urban water transfer projects are under discussion.